Interlobular Arteries From 2-Kidney, 1-Clip Goldblatt Hypertensive Rats' Exhibit-Impaired Vasodilator Response to Epoxyeicosatrienoic Acids - Sporková, Alexandra; Reddy, Rami N; Falck, John R; Imig, John D; Kopkan, Libor; Sadowski, Janusz; Červenka, Luděk (The American journal of the medical sciences, 2016)
BACKGROUND: Small renal arteries have a significant role in the regulation of renal hemodynamics and blood pressure (BP). To study potential changes in the regulation of vascular function in hypertension, we examined renal vasodilatory responses of small arteries from nonclipped kidneys of the 2-kidney, 1-clip Goldblatt hypertensive rats to native epoxyeicosatrienoic acids (EETs) that are believed to be involved in the regulation of renal vascular function and BP. A total of 2 newly synthesized EET analogues were also examined. MATERIALS AND METHODS: Renal interlobular arteries isolated from the nonclipped kidneys on day 28 after clipping were preconstricted with phenylephrine, pressurized and the effects of a 14,15-EET analogue, native 14,15-EET and 11,12-ether-EET-8ZE, an analogue of 11,12-EET, on the vascular diameter were determined and compared to the responses of arteries from the kidneys of sham-operated rats. RESULTS: In the arteries from nonclipped kidneys isolated in the maintenance phase of Goldblatt hypertension, the maximal vasodilatory response to 14,15-EET analogue was 30.1 ± 2.8% versus 49.8 ± 7.2% in sham-operated rats; the respective values for 11,12-ther-EET-8ZE were 31.4 ± 6.4% versus 80.4 ± 6%, and for native EETs they were 41.7 ± 6.6% versus 62.8 ± 4.4% (P ≤ 0.05 for each difference). CONCLUSIONS: We propose that reduced vasodilatory action and decreased intrarenal bioavailability of EETs combined with intrarenal angiotensin II levels that are inappropriately high for hypertensive rats underlie functional derangements of the nonclipped kidneys of 2-kidney, 1-clip Goldblatt hypertensive rats. These derangements could play an important role in pathophysiology of sustained BP elevation observed in this animal model of human renovascular hypertension.
Keywords: vazodilatace; 8,11,14-Eicosatrienoic Acid; Vasodilatory responses; Hypertension, Renovascular; Vasodilation; vazodilatancia; ledviny; kyselina 8,11,14-eikosatrienová; 1-Clip Goldblatt hypertension; Kidney; krysa rodu Rattus; zvířata; arteria renalis; potkani Sprague-Dawley; Male; Epoxyeicosatrienoic acids; Rats; Rats, Sprague-Dawley; 2-Kidney; Animals; Renovascular hypertension; Vasodilator Agents; mužské pohlaví; renovaskulární hypertenze; Renal Artery